Bioleaching of sand by the fungus fusarium oxysporum as a means of producing extracellular silica nanoparticles - Bansal, Vipul; Sanyal, A.; Rautaray, D.; Ahmad, Absar; Sastry, Murali (Advanced Materials, 2005)
A plant pathogenic fungus, Fusarium oxysporum, can be used as a biological model system for the extracellular bioleaching of hollow spherical silica nanoparticles (see Figure) from sand. The room-temperature synthesis of oxide nanomaterials using microorganisms starting from potential waste materials could lead to eco-friendly and economically viable methods for the large-scale synthesis of nanomaterials.

Biological synthesis of stable vaterite crystals by the reaction of calcium ions with germinating chickpea seeds - Rautaray, D.; Sanyal, A.; Bharde, Atul A.; Ahmad, Absar; Sastry, M. (Crystal Growth & Design, 2005)
The total biological synthesis of CaCO3 crystals of the metastable vaterite polymorph at room temperature by simple protein-mediated reaction of aqueous Ca2+ ions with the CO2 generated during the root growth from germinating chickpea (Cicer arietinum) seeds is described. Highly stable vaterite crystals of spherical morphology are obtained, indicating that the proteins secreted from the roots during growth play a crucial role in stabilizing and directing the crystal growth.

Calcite growth in Cissus quadrangularis plant extract, a traditional Indian bone-healing aid - Sanyal, A.; Ahmad, Absar; Sastry, M. (Current Science, 2005)
Cissus quadrangularis, a plant that has been customarily used in the Indian subcontinent to hasten the process of healing in bone fractures, has been studied and exploited to synthesize calcite crystals. The plant extract serves as a rich source of calcium ions, which when reacted with CO2, leads to the formation of calcite crystals of highly irregular morphology indicating that bioorganic molecules present in the extract modulate the crystal morphology.
Keywords: bone fracture; calcite crystals; Cissus quadrangularis; traditional healing

Fungus-mediated biosynthesis of silica and titania particles - Bansal, Vipul; Rautaray, D.; Bharde, Atul A.; Ahire, Kedar C.; Sanyal, A.; Ahmad, Absar; Sastry, Murali (Journal of Materials Chemistry, 2005)
The synthesis of inorganic materials by biological systems is characterized by processes that occur at close to ambient temperatures, pressures and neutral pH. This is exemplified by biosilicification in marine organisms such as diatoms while laboratory-based synthesis of silica involves extreme temperature and pH conditions. We show here that silica and titania particles may be produced by challenging the fungus Fusarium oxysporum with aqueous anionic complexes SiF62- and TiF62- respectively. Extra-cellular protein-mediated hydrolysis of the anionic complexes results in the facile room temperature synthesis of crystalline titania particles while calcination at 300 degrees C is required for crystallization of silica.

Heavy-metal remediation by a fungus as a means of production of lead and cadmium carbonate crystals - Sanyal, A.; Rautaray, D.; Bansal, Vipul; Ahmad, Absar; Sastry, Murali (Langmuir, 2005)
We show here that reaction of the fungus, Fusarium oxysporum, with the aqueous heavy-metal ions Pb2+ and Cd2+ results in the one-step formation of the corresponding metal carbonates. The metal carbonates are formed by reaction of the heavy-metal ions with CO2 produced by the fungus during metabolism and thus provide a completely biological method for production of crystals of metal carbonates. The PbCO3 and CdCO3 crystals thus produced have interesting morphologies that are shown to arise because of interaction of the growing crystals with specific proteins secreted by the fungus during reaction. An additional advantage of this approach is that the reaction leads to detoxification of the aqueous solution and could have immense potential for bioremediation of heavy metals. Under conditions of this study, the metal ions are not toxic to the fungus, which readily grows after exposure to the metal ions.

Synthesis and assembly of gold nanoparticles in quasi-linear lysine-keggin-ion colloidal particles - Sanyal, A.; Mandal, Sujata; Sastry, M. (Advanced Functional Materials, 2005)
The formation of fiber-like colloidal particles of the amino acid lysine complexed with Keggin ions is demonstrated. The lysine-phosphotungstic acid (PTA) colloidal particles act as excellent templates for the synthesis and assembly of gold nanoparticles wherein the lysine-PTA complex acts as a UV-switchable reducing agent for gold ions. This novel bio-organic-inorganic template shows excellent potential as a regulated nanoreactor for application in programmed nanoparticle synthesis and assembly in a single step.